Zinc (Zn) as the predominant heavy metal in ship ballast water: a case study of the Laksamana Muda John Lie Vessel - Adista D. Pramassetya; Natalie D.C. Rumampuk; James J.H Paulus; Vivanda O.J Modaso; Deiske A. Sumilat; Markus Talintukan Lasut (AQUATIC SCIENCE & MANAGEMENT, 2026)
Ballast water is essential for ship stability and navigational safety, yet it can facilitate the transboundary transport of chemical pollutants, including heavy metals. This study investigated the concentrations of lead (Pb), cadmium (Cd), copper (Cu), zinc (Zn), and nickel (Ni) in source seawater, pre-voyage ballast water, post-voyage ballast water, and destination seawater associated with the Laksamana Muda John Lie vessel. A quantitative before-after descriptive design was employed, with 14 samples collected across four conditions in triplicate, plus two controls. Temperature, pH, and salinity were measured as supporting parameters, while heavy metals were analyzed using ICP-MS following APHA Method 3125 after 0.45 µm membrane filtration at the WLN Laboratory. Results showed that Pb, Cd, Cu, and Ni were predominantly below detection limits across all sampling points. Zinc, however, was consistently detected in all conditions. Mean Zn concentrations in source seawater, pre-voyage ballast water, post-voyage ballast water, and destination seawater were 0.023, 0.275, 0.159, and 0.039 mg/L, respectively. Zn levels in ballast water exceeded the port water quality standard of 0.1 mg/L, indicating a potential pollution concern. Nevertheless, Wilcoxon signed-rank tests revealed no statistically significant differences in Zn concentrations across sampling stages (p = 0.109). These findings confirm that Zn is the predominant trace metal of concern in the studied ballast water, though its concentration remains relatively stable throughout the voyage. The study emphasizes the importance of routine Zn monitoring in ballast water and advocates for stricter discharge regulations to mitigate heavy metal pollution from maritime operations.